Pengaruh Penggunaan Tiktok Terhadap Perilaku Konsumtif Mahasiswa Di Yogyakarta - Adrenajoys Brilliand Mayfalessy Jovanoti; Daffa Syauqi Rahman; Muhammad Shidqi Daffa Baihaqi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study examines the influence of TikTok usage on the consumptive behavior of students in Yogyakarta. TikTok has evolved into a digital communication platform that not only functions as entertainment but also plays a role in shaping attitudes, perceptions, and consumption patterns among young audiences. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to students who actively use TikTok and analyzed using SPSS. The results show that TikTok usage has a positive and significant effect on students’ consumptive behavior. The coefficient of determination indicates that TikTok contributes substantially to shaping students’ consumption patterns, while the remaining influence is explained by other factors outside this study. These findings confirm that TikTok acts as a persuasive communication medium that has a real impact on student consumption behavior in the digital era.